Citrus - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Citrus by FS Davies and L G Albrigo 1994 272pp ISBN 0 85198 867 9 Price UKL19.95 CAB International, Wallingford,Oxon OX10 8DE